Normative Velopharyngeal Data in Infants: Implications for Treatment of Cleft Palate. Issue 6 (September 2016) - Schenck, Graham C.; Perry, Jamie L.; Fang, Xiangming
Abstract : Abstract: Identifying normative data related to velopharyngeal muscles and structures may have clinical significance for infants born with cleft palate, especially as they relate to selection of surgical intervention and postsurgical outcomes. Previous studies suggest that patients whose anatomy postsurgically is dissimilar to that of their normative counterparts are at risk for hypernasal speech. However, studies have not documented what constitutes "normal" anatomy for the clinically relevant population—that is, the infant population. The purpose of this study is to examine a magnetic resonance imaging database (n = 29) related to normative velopharyngeal structures and provide a preliminary comparison to 2 selected patients with repaired cleft palate. Twenty-nine healthy infants between 9 and 23 months of age (mean = 15.2 months) with normal craniofacial and velopharyngeal anatomy were recruited to participate in this study. Normative data were compared to 2 infants with repaired cleft palate between 13 and 15 months of age (mean = 14 months). Quantitative craniometric and velopharyngeal measures from the sagittal and oblique coronal image planes were collected. Variables of interest included: levator muscle, velar, and craniometric measures. Females demonstrated significantly larger intravelar segments compared with males. White infants demonstrated significantly larger levator muscles compared to non-white infants. Infants with repaired cleft palate demonstrated increased overall levator muscle length and levator extravelar length compared with infants with normal velopharyngeal anatomy. Data from the present study provide a normative database for future investigators to utilize as a comparative tool when evaluating infants with normal and abnormal velopharyngeal anatomy.